Pengaruh Kombinasi Kulit Semangka (Citrullus lanatus) Dan Jambu Biji Merah (Psidium guajava) Terhadap Kualitas Selai Lembaran - Tiurma Wiliana Susanti Panjaitan; Dwi Agustiyah Rosida (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2021)
Producing fruit leather in Indonesia is still rarely done in the food industry, even though it is hoped to make bread presentation problems more practical. Fruit leather can be made from fruits, such as using watermelon skin (albedo) which is often discarded even though the pectin content is high. Watermelon rind has a color, taste and aroma that is less attractive, so it needs to be combined with red guava because it has a distinctive color, taste and aroma. This study aims to identify the effect of the combination of watermelon skin and red guava on sheet jam's chemical, physical, and organoleptic characteristics. Also, to determine the most preferred combination based on organoleptic tests. The study used a completely randomized design with 1 factor: a combination of watermelon skin and red guava with 4 levels of treatment : P1 (20% : 80%), P2 (30% : 70%), P3 (40% : 60%) dan P4 (50% : 50%). Parameters observed were water content, pectin content, pH, ash content, reducing sugar content, total dissolved solids and texture. This data is analyzed by Analysis of Variance and the smallest significant difference (if there is a difference). The organoleptic test was carried out on 44 panelists (untrained) covering taste, color, aroma and texture using five levels of preference scale: very dislike (1), dislike (2), neutral (3), like (4) and very like (5). The formulation with the use of more watermelon skin and less red guava resulted in an increase in water content and pectin content, the texture was more supple. On the other hand, reducing sugar content, total dissolved solids and ash content decreased. In terms of color and taste, panelists prefer P1 and P2 treatments. Regarding aroma, the four treatments received relatively the same response, as for texture, panelists prefer the P3 treatment, therefore the recommended combination is treatment P1 and P2. Keywords: fruit leather, watermelon skin, guava, jam quality, organoleptic test